Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosques secos colombianos en la Colección Entomológica del Instituto Alexander von Humboldt (2016)
This reports includes the records of dung beetles associated with the dry forests of Colombia present at the Entomological Collection of the Instituto de Investigación de Recursos Biológicos Alexander von Humboldt. The data set includes 11686 records, 19797 specimens belonging to 18 genera and 68 species. The species sorting included an exhaustive study of the external morphology and male genitalia. For species identification, updated taxonomic revisions, original descriptions, re-descriptions, and regional revisions were used. It was possible to identify 35 to species (genus and species names), and another 33 species were assigned a unique morpho-species code identifier after the generic name was determined (morph-species code). The lack of recent taxonomic revisions in genera such as Canthon, Canthidium, Dichotomius, Uroxys and Onthophagus has limited the identification to specific level in Colombia; a reason for the incomplete and imprecise species list that had been published. This data set supports the most complete and verified species list of dung beetles of the dry forests of Colombia.